Direct Isolation Method for Tomato-Infecting Phytophthora infestans : Metode Isolasi Langsung untuk Phytophthora infestans yang Menginfeksi Tanaman Tomat - Parlindo, Fitra; Khairani, Hagia Sophia; Papona, Alisya Talita; Tondok, Efi Toding (Jurnal Fitopatologi Indonesia, 2024)
Infection of Phytophthora infestans at high altitudes in tropical regions causes symptoms of tomato late blight throughout the year. Even though it is very easy to find in the field, P. infestans is often very difficult to isolate aseptically in the laboratory. This study aims to evaluate direct isolation techniques that can increase the success of isolating P. infestans. Isolation was carried out on a non-specific medium, consisting of potato dextrose agar (PDA), corn meal agar (CMA), oatmeal agar (OMA), and water agar (WA) with three alternative types of antibiotics, i.e. chloramphenicol, amoxicillin, and rifampicin. Observations were carried out to determine the effect of the medium on sporangia induction and the age of the original colony’s growth in CMA and OMA media. The results showed that the isolation of P. infestans using the direct method was successfully carried out on non-specific PDA, CMA, OMA and WA medium. The highest isolation success rate was obtained on CMA medium with the addition of 50 mg L-1 rifampicin. The fastest sporangia induction (8 days) was shown by colonies grown on OMA medium with the addition of 50 mg L-1 rifampicin based on the category of abundant sporangia after 20 days of incubation. Rejuvenation of P. infestans colonies for research purposes in the laboratory is recommended to be carried out routinely twice a month. This research provides practical guidance for understanding the bioecology of P. infestans infecting tomato plants, especially for further study on oomycetes fungi.